The Effect of Inflation and Unemployment Rate on Economic Growth Rate in North Sumatra (Period 2013-2022) - Noer, Muhammad Raihan; Damara, Muhammad Deni; Runi, Naila Ananda; Nafisha, Nadya; Fayza, Salsabila; Silaban, Putri Sari Margaret Julianti (Perpustakaan dan Penerbitan Unismuh Makassar, 2024)
This research aims to determine the effect of changes in the inflation rate and unemployment rate on the rate of economic growth in the province of North Sumatra over a 10 year period. The technique for collecting data is secondary methods through the Indonesian Central Statistics Agency. The method used to test the relationship between the independent variable and the dependent variable is the classic SPSS assumption test with multiple linear regression measurements. This research resulted in 1) The inflation rate during the research period did not have a significant effect on changes in the rate of economic growth. 2) The changing unemployment rate also does not have a significant influence on changes in the level of economic growth in North Sumatra. The author hopes that further research can further increase assumptions and knowledge, especially variables that can explain the influence of inflation and unemployment rates on more recent levels of economic growth.